Downstream consequences of pubertal timing for young women's body beliefs. (April 2019) - Grower, Petal; Ward, L. Monique; Beltz, Adriene M.
Abstract: Introduction: Puberty is a critical biopsychosocial event that has long-term consequences for adolescents' behavior and well-being. Research has shown that developing earlier than one's peers may worsen adolescent girls' body image, in part due to weight redistribution and increases in adiposity resulting from pubertal development. However, research has yet to examine if pubertal timing is associated with girls' body beliefs related to self-objectification, self-sexualization, and positive body image beyond the adolescent years. We address that issue here. Methods: Participants were 287 undergraduate White women (Mage = 18.62, SDage = 0.93) from the United States who completed surveys containing a retrospective report of pubertal timing and several scales assessing their current body beliefs. Results: Regression analyses demonstrated that earlier pubertal timing was linked to greater body surveillance, greater sex appeal self-worth, and less body appreciation, but not to body shame or enjoyment of sexualization, which were negatively related to age. Conclusions: This study provides preliminary evidence that pubertal timing has downstream consequences for a variety of women's body beliefs. However, older women reported less body shame and less enjoyment of sexualization than younger women, suggesting possible age (and not puberty-) related developmental trends in these two body beliefs. These findings highlight a need for future work with larger, more diverse samples and longitudinal data.